2020
DOI: 10.1111/hsc.13009
|View full text |Cite
|
Sign up to set email alerts
|

Usual source of care and experiences with primary care among community health service centre patients in Changchun, China: A cross‐sectional survey

Abstract: Under China's healthcare reforms, community health service centres (CHCs) have been established as the preferred primary care providers. Even with this change, there is still little attention paid to patients' usual source of care (USC) from CHCs in Northeastern China. The main purposes of this study were to explore the determinants of usual source of community health service and to examine the association between usual source of community health service and patients' experiences with primary care. A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…With respect to the determinants of PHC preference, we found that residents with poor health status or chronic disease were less likely to choose the PHC services in China. This finding is inconsistent with the study of patients' experience with PHC in Changchun in China, indicating that patients with poor health status or chronic disease were more likely to choose PHC [2]. The possible explanations for this finding might be that it was caused by the differences in study sample.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…With respect to the determinants of PHC preference, we found that residents with poor health status or chronic disease were less likely to choose the PHC services in China. This finding is inconsistent with the study of patients' experience with PHC in Changchun in China, indicating that patients with poor health status or chronic disease were more likely to choose PHC [2]. The possible explanations for this finding might be that it was caused by the differences in study sample.…”
Section: Discussioncontrasting
confidence: 78%
“…During the past decade of healthcare reform, China has made great efforts to improve the Primary Health Care (PHC) system [1], especially to strengthen the construction of PHC delivery system. In China, the PHC institutions consist of community healthcare centers/stations in urban areas, township hospitals, and village clinics in rural areas [2]. They provide general disease diagnosis, treatment services, and essential public health services [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As well as improving drug accessibility for poor patients and lowering their treatment financial burden, the government’s centralized drug procurement should be further expanded; a reasonable range of medications, more technologies, and innovative medicines should be added to meet the people’s demand for high quality [ 46 ]. Moreover, simply adding more health workers will not suffice, as a strong foundation for trusting relationships within the workforce needs to be strengthened, supported by high-quality training, strong and effective supervision, and appropriate compensation [ 47 ]. To achieve this, team-based approaches could be considered a promising way to scale quality, patient-centered primary care services; inclusive of family doctors and community health workers being actively engaged with patients and their families in healthcare delivery [ 48 ].…”
Section: Discussionmentioning
confidence: 99%